Targeting the PI3K/STAT3 axis modulates age‐related differences in macrophage phenotype in rats with myocardial infarction. Issue 9 (17th July 2019) - Lin, Chih‐Chan; Chen, Syue‐yi; Lien, Hsiao‐Yin; Lin, Shinn‐Zong; Lee, Tsung‐Ming
Abstract: Ageing is associated with impaired repair mechanisms in cardiovascular diseases. Macrophages contribute to cardiac fibrosis after myocardial infarction (MI). The phosphatidyl‐inositol‐3‐kinase (PI3K) pathway has been shown to play a role in cardiac remodelling after MI. It remained unclear whether n ‐butylidenephthalide, a major component of Angelica sinensis, can attenuate cardiac fibrosis by regulating the PI3K/signal transducer and activator of transcription 3 (STAT3)‐mediated macrophage phenotypes in ageing rats after MI. Twenty‐four hours after ligation of the left anterior descending artery, young (2‐month‐old) and ageing (18‐month‐old) male Wistar rats were treated with either vehicle or n ‐butylidenephthalide for 4 weeks. There were similar infarct sizes in both age groups. Compared with young rats, ageing rats exhibited significant increased cardiac fibrosis after MI, which can be attenuated after administering n ‐butylidenephthalide. MI was associated with decreased activities of PI3K and STAT3 in ageing rats compared with young rats. In both age groups, n ‐butylidenephthalide effectively provided a significant increase of STAT3 phosphorylation, STAT3 activity, STAT3 nuclear translocation, myocardial IL‐10 levels and the percentage of M2c macrophage and a decrease of myofibroblast infiltration. The effects of n ‐butylidenephthalide on increased IL‐10 levels were reversed by LY294002 or S3I‐201. Furthermore, LY294002 abolished the STAT3 phosphorylation, whereas PI3K activity was not affected following the inhibition of STAT3. In conclusions, the host environment is responsible for ageing‐related myofibroblast dysregulation in response to MI which can be improved by administering n ‐butylidenephthalide via macrophage differentiation towards M2 phenotype by targeting the PI3K/STAT3 axis.